Changes in amino acid and nucleotide pools of Rhodospirillum rubrum during switch-off of nitrogenase activity initiated by NH4+ or darkness. - Li, J D (1987)
Amino acid and nucleotide pools were measured in nitrogenase-containing Rhodospirillum rubrum cultures during NH4+- or dark-induced inactivation (switch-off) of the Fe protein. A big increase in the glutamine pool size preceded NH4+ switch-off of nitrogenase activity, but the glutamine pool remained unchanged during dark switch-off. Furthermore, methionine sulfoximine had no effect on the rate of dark switch-off, suggesting that glutamine plays no role in this process. In the absence of NH4+ azaserine, an inhibitor of glutamate synthate, raised glutamine pool levels sufficiently to initiate switch-off in vivo. While added NH4+ substantially increased the size of the nucleotide pools in N-limited cells, the kinetics of nucleotide synthesis were all similar and followed (rather than preceded) Fe protein inactivation. Darkness had little effect on nucleotide pool sizes. Glutamate pool sizes were also found to be important in NH4+ switch-off because of the role of this molecule as a glutamine precursor. Much of the diversity reported in the observations on NH4+ switch-off appears to be due to variations in glutamate pool sizes prior to the NH4+ shock. The nitrogen nutritional background is an important factor in determining whether darkness initiates nitrogenase switch-off; however, no link has yet been established between this and NH4+ (glutamine) switch-off.